Economic stimulus and financial instability: Recent case of the U.S. household - Youngna Choi (Journal of Risk and Financial Management, 2022)
The effectiveness of government policies and economic stimuli during the 2007 financial crisis and the COVID-19 pandemic are compared in this study. While the 2007 financial crisis started in the real estate market and spread through the contagion effect to other sectors, the pandemic halted the all sectors of the global economy simultaneously. In the United States, where the social safety net is not as strong as other advanced economies, the unemployment rate skyrocketed and many families lost income. The federal government countered with various relief packages, which have been, unlike the rounds of quantitative easing prevalent after the 2007 financial crisis, direct payments to households and businesses. The Agent Instability Indicator and default elasticity coefficient are used to quantitatively assess the financial instability and default risk of subgroups of United States households classified by percentile of income and net worth. It turns out that the financial instability level of the United States household during the pandemic has not been as high as that during the 2007 crisis and the Great Recession. It is concluded that the direct handout of cash-so called helicopter money-is more effective at preventing financial collapse and stabilizing the economy than quantitative easing through asset purchase.
Keywords: 650; COVID-19 pandemic; financial instability; helicopter money; quantitative easing